Shallot (Allium cepa L.) Growth and Yield under Nitrogen and Phosphorus Fertilization in Former Long Bean Fields - Janah, Miftahul; Azhari, Anjar Pranggawan; Jufri, Afifah Farida (Jurnal Biologi Tropis, 2026)
Shallot (Allium cepa L.) is a high-value horticultural crop whose productivity depends on adequate nutrient availability and fertilizer management. Former yardlong bean land has the potential to improve fertilizer efficiency through residual nitrogen derived from biological nitrogen fixation. This study aimed to evaluate the effects of nitrogen (N) and phosphorus (P) fertilizer rates and their interaction on the growth and yield of shallot cultivated on former yardlong bean land. Four nitrogen rates (25%, 50%, 75%, and 100% of the recommended dose) and two phosphorus rates (50% and 100% of the recommended dose), each replicated three times, were used in the factorial Randomized Complete Block Design experiment, which was carried out in Rembige Village, Mataram City, between February and April of 2026. Analysis of variance and the Honestly Significant Difference test at the 5% significance level were used to evaluate the data. At 42 and 49 days following planting, nitrogen had a substantial impact on both the number of bulbs per clump and plant height. While the interplay between nitrogen and phosphorus had a substantial impact on leaf chlorophyll content, phosphorus had a considerable impact on bulb number, bulb diameter, and fresh bulb weight. The combination of 75–100% recommended nitrogen and 100% recommended phosphorus produced the best growth and yield, indicating that former yardlong bean land can enhance fertilizer use efficiency in shallot cultivation.